Kesetaraan Gender dalam Perspektif Islam dan Kristen - Hasibuan, Derlina Sari; Harahap, Aprilinda M.; Utomo, Wahyu Wiji (ANWARUL, 2023)
This study discusses "Gender Equality in Islamic and Christian Perspectives". Gender equality is a goal that must be achieved by all human beings in the world, so that no one feels that they are better than others. Gender injustice is a system or structure in which both men and women become victims of the system. In this study using the method of library research (library research). The source of research data is primary data obtained in the Al-Quran and the Bible (gospel). And secondary data, namely those whose sources are obtained from books, journals, articles. The results of this study indicate that gender is a perspective that distinguishes the roles of men and women, gender equality in the content of this material is in the form of sentences showing equal access and opportunities between men and women in various activities, fulfillment of rights and responsibilities without any differences in treatment between both. In Islam, women and men are both servants of Allah SWT, the only difference is their piety. In Christianity women and men are said to be in the image of God and need each other.